2018
DOI: 10.1002/ncp.10067
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Changes in Handgrip Strength in Children With Cystic Fibrosis: A Pilot Study

Abstract: HGS z scores and FEV significantly increased at follow-up. HGS z scores were lower than the standard even though mean BMI z scores classified participants as normal nutrition status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 33 publications
(113 reference statements)
1
22
0
Order By: Relevance
“…As mentioned earlier, DEXA scans provide information on body composition, which has important implications on BMD. LBM was found to be more strongly associated with pulmonary functions than BMI 29 . HGS is reflective of LBM.…”
Section: Discussionmentioning
confidence: 82%
“…As mentioned earlier, DEXA scans provide information on body composition, which has important implications on BMD. LBM was found to be more strongly associated with pulmonary functions than BMI 29 . HGS is reflective of LBM.…”
Section: Discussionmentioning
confidence: 82%
“…6,7 Findings such as these have led to a growing interest in measuring body composition in individuals with CF; however, the various measurement methods are often unreliable, too costly, or not feasible in the CF population. 8 Dual energy x-ray absorptiometry (DEXA), hydrostatic weighing, and air displacement plethysmography are reliable gold standards for measuring body composition, but they are costly and, particularly in the case of hydrostatic weighing, not clinically feasible. Using triceps skin fold and mid-arm circumference measurements to calculate arm muscle area has a wide margin of error, and measurements are often unreliable because of low interrater reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Using triceps skin fold and mid-arm circumference measurements to calculate arm muscle area has a wide margin of error, and measurements are often unreliable because of low interrater reliability. 8 Bioelectrical impedance analysis (BIA), even when using the more expensive multifrequency BIA machines ($5000-$19,000 USD), also have reliability issues. A recent validation study of 110 recreationally active adults aged 18-25 years found that BIA measured a 4%-9% difference in percent body fat compared with DEXA, with BIA tending to underestimate percent body fat compared with DEXA.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations